Sleep quality and associated factors among police officers in Northwest Ethiopia: a cross-sectional study - Zelalem Birhan; Fikir Addisu; Temesgen Ergetie; Wubalem Fekadu; Nigusie Abebaw; Tamrat Anbesaw; Asmare Belete; Bogale Birhanu (Sleep Science and Practice)
Abstract Background Police officers are particularly vulnerable to poor sleep quality, which can have a serious detrimental impact on their health because of the numerous stressors they deal with on a daily basis. Therefore, police officers who suffer from sleep problems and do not receive proper diagnosis and treatment may perform less well at work, which could endanger both their own safety and the protection of the community they serve. The purpose of this study was to evaluate the prevalence of poor sleep quality and its associated factors among police officers in Bahirdar city, Northwest Ethiopia. Methods An institutional-based cross-sectional study was conducted among police officers in Bahirdar City. A total of 422 police officers were selected by a simple random sampling method. Sleep quality was assessed by using the Pittsburgh Sleep Quality Index. The associated factors were measured using multivariable logistic regressions. Odds ratios, 95% CIs, and p-values less than 0.05 were used to characterize the relationships between the variables. Result The prevalence of poor sleep quality was 42.9% (95% CI; 38.2, 46.7). Odds of being female (AOR: 4.85, 95% CI; 2.46, 9.53), single (AOR:4.55, 95% CI; 2.36, 8.78), having poor social support (AOR: 5.28, 95% CI; 2.93, 9.51), having depressive symptoms (AOR:4.40, 95% CI; 2.30, 8.41), experiencing Post-Traumatic Stress Disorder (AOR: 4.63, 95% CI; 1.88, 11.39), having moderate stress (AOR: 2.66, 95% CI; 1.42, 4.37), and severe stress (AOR: 5.32, 95% CI; 2.45, 9.13) were significantly associated with poor sleep quality. Conclusions Poor sleep quality was found to be highly prevalent among police officers in Bahir Dar city. Approximately 43% of the police officers reported having trouble sleeping. These results suggest that the need for targeted intervention to cope with sleep disturbance is necessary; police officers require proper psychosocial intervention programs and sleep health promotion, focusing specifically on female officers, single officers, those with low social support networks, and those exhibiting symptoms of depression and post-traumatic stress disorder.